2017
DOI: 10.1063/1.4990536
|View full text |Cite
|
Sign up to set email alerts
|

Fine tuning classical and quantum molecular dynamics using a generalized Langevin equation

Abstract: Generalized Langevin Equation (GLE) thermostats have been used very effectively as a tool to manipulate and optimize the sampling of thermodynamic ensembles and the associated static properties. Here we show that a similar, exquisite level of control can be achieved for the dynamical properties computed from thermostatted trajectories. We develop quantitative measures of the disturbance induced by the GLE to the Hamiltonian dynamics of a harmonic oscillator, and show that these analytical results accurately pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(129 citation statements)
references
References 45 publications
1
128
0
Order By: Relevance
“…Though the result has been derived under a harmonic approximation, the predictions happen to be in excellent agreement with the exact VACF for system as anharmonic as liquid water [21]. It was shown that the post-processing deconvolution of the perturbed spectra can properly recover the unperturbed dynamic properties even in the case of heavily thermostatted cases, i.e.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Though the result has been derived under a harmonic approximation, the predictions happen to be in excellent agreement with the exact VACF for system as anharmonic as liquid water [21]. It was shown that the post-processing deconvolution of the perturbed spectra can properly recover the unperturbed dynamic properties even in the case of heavily thermostatted cases, i.e.…”
Section: Introductionmentioning
confidence: 84%
“…where ζ(t) is a time-correlation function of the random force and K(t), is the memory kernel, introducing the dependence of the system evolution on its history in terms of a non-Markovian stochastic differential equation [21]. Such definition, however, requires the use of integrodifferential equations, leading to a serious numerical challenge.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations